Managerial Implementation of Private Private Communication to Improve Teacher Performance through Clinical Supervision at Santa Lusia Private Elementary School, Sei Rotan - Ester Justina Sinaga; Rosnelli Rosnelli; Wildansyah Lubis; Nathanael Sitanggang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The three main elements in teaching and learning activities are teachers, students and schools. If a school principal has good communication skills with teachers, it is not impossible that it will improve teacher performance. Supervision activities are carried out in an effort to improve and control all activities so that they are carried out optimally. The purpose of this study was to determine the effect of the principal's managerial competence on improving teacher performance through clinical supervision at SDS Santa Lucia Sei Rotan. The research subjects for this school action research were teachers at the Santa Lucia Sei Rotan Private Elementary School who were active in learning activities with a total of 15 people who actively taught in semester II of the 2022/2023 school year. This research was conducted at Santa Lucia Private Elementary School located on Jl. Medan-Batang Quiz KM 14 No. 123 Sei Rattan, Kec. Percut Sei Tuan Kab. Deli Serdang Prov. North Sumatra 20371. and the time of this research is planned for 3 months in March-May 2023. The data collection technique used in this research is observation and documentation. The research instrument uses a sheet of teacher assessment criteria. The data analysis used in this study is a comparative descriptive analysis technique. The results showed 2. The data analysis used in this study is a comparative descriptive analysis technique. The results showed 2. The data analysis used in this study is a comparative descriptive analysis technique. The results showed 2.     In cycle II of 15 teachers who attended clinical supervision through the Principal's communication, the teacher's performance score was 8 (53%) teachers got Very Good scores, 6 (40%) teachers got Good scores, 1 (7%) teachers got Fair scores , no teacher got Less and Failed grades.